Serum Magnesium Level In Toxemias Of Pregnancy - DR. B. VODELU; DR. S. LAXMI NARAYANA (International Journal of Pharma and Bio Sciences, 2015)
The cases for the present study were selected from the antenatal outpatient, Gandhi Hospital, Secunderabad, Telangana, India, according to specific criteria like women with age group between 18-28 years, primigravide with known last menstrual period and gestational age between 20-30 weeks. A total of 34 subjects were selected in this study, out of which 22 were Pregnancy Induced Hypertensive (B.P. >140/90 mmHg), who were considered as the experimental group and remaining 12 were normotensive (B.P. <140/90 mmHg) taken as controls. The experimental group was further categorized into two groups, having 16 women with preeclampsia (Group II) and six were eclampsia (Group III). Serum magnesium levels were estimated utilizing the calorimetric method. The mean serum magnesium level in preeclampsia (Group II) and eclampsia (Group II) was 1.81±0.14 and 1.74 ± 0.036mg/dl respectively. About 43.75% of the preeclampsia and 83.33% of the eclampsia women had serum magnesium level less than 1.80 mg/dl. The serum magnesium levels were observed to be decreased in pregnancy. A significant decrease in serum magnesium levels was observed in the experimental group III (eclampsia). Whereas, in pre-eclampsia though there was a marked decrease in serum magnesium level, the decreases were not statistically significant. The prevalence of magnesium deficiency status was higher among the pregnancy women in the present study.